Cyber-physical motion of digital human model for connected society. (2018) - Ito, Teruaki; Watanabe, Tomio
The rapid movement towards the connected society requires faster and adaptive decision making to comply with the frequent and unexpected changes in the environment. Not only the theoretical thinking but also the emotional interaction is the key of decision-making process in the connected society. This paper proposes an idea of cyber-physical communication media through the active motion of computer display, which would further strengthen the connection between people in terms of emotional aspect of communication. Using the digital human model of mid-air head motion as well as that of mid-air hand gestures, implementation of the idea is presented in this paper. According to the experimental results, feasibility of cyber-physical motion is discussed for video communication system applications.